A possibilidade de celebração e de controle de acordos coletivos promovidos por associações - Neman Mancilha Murad (2022)
The research aims to analyze if associations may utilize the adequate methods of conflict resolution to prevent or end collective conflicts about homogeneous individual rights; and suggest means of controlling the settlements’ adequacy. To achieve this, theoretical research was developed, starting with the analysis of the associations’ main characteristics, and the comparison between civil associations and unions. The legitimacy given to public agencies and private entities to act as representatives in class actions and the distinction of collective rights between diffuse, collective, and homogeneous individual rights by the Brazilian integrated legal system. The study´s theoretical framework was Ludmila Costa Reis’ conception of Extra-judicial collective process, and two research focuses were established: from the subjective standpoint, the analysis considered civil associations; and from the objective standpoint, emphasis was given to the possibility of settlement in class actions discussing homogeneous individual rights. These choices were made because civil associations are the subject of less studies and are the most adequate representative in Class Actions regarding homogeneous individual rights. The study confirmed the hypothesis that the individual norms that stimulate the use of settlements in individual conflicts are compatible with Brazil’s integrated system of norms which regulates Class Actions and defended the possibility of associations celebrating settlements to end collective conflicts. It also verified that the Class Action settlement is broader than Brazil’s Conduct Adjustment Agreement and seem to be the most adequate instrument to formalize consensus regarding homogeneous individual rights. It also concluded that means of controlling the adequacy of settlements made by associations are needed, identifying the possibility of a judicial control of the association’s adequacy of representation, the intervention of other collective representants, and the judicial control of the settlement’s content. Besides, instruments to ensure the participation of the biggest possible number of affected people in the process of achieving consensus are necessary. Finally, the research concluded that the secundum eventum litis res judicata system can discourage the use of settlement, since the individuals can propose individual lawsuits to opt out of the settlement’s terms. Therefore, the creation of a system that stimulates the use of settlements regarding homogeneous individual rights depends on legal alterations, which may be discussed from the starting point of the propositions currently being processed in Brazil’s Congress.